Dipeptidyl peptidase IV-like molecules: homologous proteins or homologous activities? - Sedo, A; Malík, R (Biochimica et biophysica acta, 2001)
Membrane-bound proteases are widely distributed among various cell systems. Their expression in a particular cell type is finely regulated, reflecting the specific functional cell implications and engagement in defined physiological pathways. Protein turnover, ontogeny, inflammation, tissue remodeling, cell migration and tumor invasion are among the many physiological and pathological events in which membrane proteases play a crucial role, both as effector as well as regulatory molecules. The presence of proline residues gives unique structural features to peptide chains, substantially influencing the susceptibility of proximal peptide bond to protease cleavage. Among the rare group of proline-specific proteases, dipeptidyl peptidase IV (DPP-IV, EC 3.4.14.5) was originally believed to be the only membrane-bound enzyme specific for proline as the penultimate residue at the amino-terminus of the polypeptide chain. However, other molecules, even structurally non-homologous with the DPP-IV but bearing corresponding enzyme activity, have been identified recently. This review summarizes the present knowledge of "DPP-IV activity- and/or structure-homologues" (DASH) and provides some insight into their multifunctional roles.
Keywords: izoenzymy; zvířata; serinové endopeptidasy; signální transdukce; dimerizace; Membrane Proteins; Signal Transduction; Animals; lidé; endopeptidasy; Dimerization; dipeptidylpeptidasa 4; Dipeptidyl Peptidase 4; Isoenzymes; T-lymfocyty; želatinasy; Humans; dipeptidasy; Endopeptidases; Structure-Activity Relationship; Serine Endopeptidases; Dipeptidases; T-Lymphocytes; membránové proteiny; vztahy mezi strukturou a aktivitou; Gelatinases